The uncertain commodity of 'security': Are private security companies 'value for money' for domestic violence services?. Issue 4 (December 2021) - Harkin, Diarmaid
Reflecting onLoader and White 's (2018) suggestion that the labour of private security workers is difficult to 'commodify', this paper uses original empirical data to show that there are four elements to what private security workers 'do' for victims of domestic violence when contracted by domestic violence advocacy services: they provide (a) practical 'target-hardening' measures, (b) 'expert' advice on security, (c) forms of 'security therapy' as workers talk clients through their safety-based anxieties and (d) forms of 'security theatre' as workers provide the appearance of providing security despite the efficacy often being unclear or uncertain. Each of these elements have significant risks that can threaten the interests of victims and domestic violence services.